2022
DOI: 10.26842/binhm.7.2022.17.1.0467
|View full text |Cite
|
Sign up to set email alerts
|

Birds of Conservation Concern at Al-Najaf Desert, Southern Desert of Iraq

Abstract: One eighth of the bird species in the world is considered globally threatened; the avifauna of Iraq comprises 409 species and is considered as the major indicator of the health of Iraq’s biological resources. The Iraqi geography falls into five main regions among which is the desert and semi-desert areas which cover much of the country area. Al-Najaf desert is still one of the poorly known regions from the biodiversity point of view. Birds of conservation concern are detected in Al-Najaf desert during 31 fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In fact, the study area embraces at least 12 species of conservation concern including the two mentioned plants, one vulnerable (VU) reptile Uromastyx aegyptia (Forskål. 1775) [55], nine birds assessed by Al-Rammahi and Mohammad [56] comprising the endangered (EN) species Falco cherrug (J.R. Gray. 1834), Aquila nipalensis (Hodgson.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the study area embraces at least 12 species of conservation concern including the two mentioned plants, one vulnerable (VU) reptile Uromastyx aegyptia (Forskål. 1775) [55], nine birds assessed by Al-Rammahi and Mohammad [56] comprising the endangered (EN) species Falco cherrug (J.R. Gray. 1834), Aquila nipalensis (Hodgson.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have acknowledged that ticks, mainly Hyalomma species, which is the principal vector of CCHF, and Rhipicephalus and Haemaphysalis (Hasson & Al-Zubaidi, 2014;Mohammad, 2016;Mallah & Rahif, 2016), commonly infest animals in Iraq. A literature review of various Medline platforms including PubMed, ProQuest, EBSCOhost, Web of Science, and Ovid regarding the distribution of tick species showed a scarcity of publications on CCHF outbreaks, especially in Iraq.…”
Section: Introductionmentioning
confidence: 99%
“…and the last factors of the indirect reasons that named anthropogenic. Moreover, it was found that the oriental hornet, Vespa orientalis Linnaeus, 1771(Hymenoptera, Vespidae); is very devastating predators of honeybees and become a limiting factor in the success of beekeeping 9]; furthermore this species is one of the most important pests aggressive and attacking A. mellifera colonies in many regions in the world [10,11], the hunting behavior of this wasp against honey bees in Iraq was also seen by Glaiim [12]. V. orientalis Linnaeus, 1771 is native to the southeastern Mediterranean, northeastern and eastern Africa, Middle East and Central Asia [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Volynchik [17] stated that the number of hornet workers comes out of the nest at the noon period more than the number of those comes out in the morning or evening period. It causes damage by destroying bee hives and by reducing or even inhibiting the flights of bees [12], which results in considerable loss for apiarists and reduced the pollination of crops; it has also become a serious pest of different fruit trees such as grape, date palm, pear, peach, ... etc.…”
Section: Introductionmentioning
confidence: 99%